Common universal behavior of magnetic domain walls driven by spin-polarized electrical current and magnetic field - Diaz Pardo, R. (2019)
We explore the universal behaviors of a magnetic domain wall driven by the spin-transfer torque of an electrical current, in a ferromagnetic (Ga,Mn)(As,P) thin film with perpendicular magnetic anisotropy. For a current transverse to the domain wall, the dynamics of the thermally activated creep regime and the depinning transition are found to be compatible with a self-consistent universal description of magnetic-field-induced domain-wall dynamics. This common universal behavior, characteristic of the so-called quenched Edwards-Wilkinson universality class, is confirmed by an independent analysis of domain-wall roughness. Complementary investigations reveal the directional properties of interaction between current and domain walls which result in the instability of their transverse orientation.